Effects of Pueraria mirifica on vaginal artery vascularization in postmenopausal women with genitourinary syndrome of menopause - Warinsiriruk P. (2023)
Objective: To compare the effects of 6% Pueraria mirifica vaginal gel with those of placebo gel on vaginal blood flow, vaginal maturation index (VMI), vaginal health index (VHI), endometrial thickness and genitourinary symptoms in postmenopausal women. Study design: In a randomized, double-blinded, placebo-controlled study (TCTR20200624007), 72 postmenopausal women were randomized into the P. mirifica or the placebo gel group. Both groups were followed up at week 4 and week 12. Main outcome measure: Doppler ultrasonography pulsatility index (PI) and resistance index (RI), VMI, VHI, endometrial thickness and genitourinary symptoms were evaluated at baseline, at week 4 and week 12 of treatment. Results: Sixty-three participants completed the study. After 4 and 12 weeks of treatment, PI and RI had significantly decreased in the P. mirifica group compared with the placebo group. At week 12, PI in the P. mirifica group and in the placebo group were 3.03 + 1.09 and 6.88 + 2.16, respectively (p = 0.002). Similar changes were also demonstrated in the resistance indices. The P. mirifica group demonstrated a markedly higher mean VMI at week 12 compared with the placebo group, 55.19 ± 18.53 and 20.29 ± 28.46 (p = 0.012). In addition, all parameters of VHI based on the vaginal physical findings at week 12 in the P. mirifica group were significantly higher than in the placebo group (p < 0.001). Conclusion: In this study, 6% P. mirifica vaginal gel for 12 weeks in postmenopausal women with GSM appeared to increase vaginal artery circulation and restore atrophic vaginal tissue. Clinical Trial Registration Number: TCTR20200624007.